JOURNEY BEYOND CASTE, ASHRAMAS AND REINCARNATION - Seidel, George J (Journal of Dharma, 1986)
The current status of the doctrine of reincarnation in Hinduism and in Buddhism is unclear. Equally unclear is how essential it is to the religions. Is it merely an unquestioned assumption? Or is it an animistic hangover from the aboriginal tribes in India before the arrival of the Ayrian invaders, as Radhakrishnan opines? In his voluminous History of Indian Philosophy Dasgupta notes that seldom before or after the Buddha is there any serious attempt made to prove or disprove the doctrine of rebirth. l According to R. C. Zaehner, it is simply accepted as a "self-evident fact".